Exploring associations of somatic symptom disorder with personality dysfunction and specific maladaptive traits - von Schrottenberg, Victoria; Kerber, André; Sterner, Philipp; Teusen, Clara; Beigel, Pauline; Linde, Klaus; Henningsen, Peter; Herpertz, Sabine; Gensichen, Jochen; Schneider, Antonius (Psychopathology, 2025)
Introduction: According to ICD-11, personality disorders (PDs) are defined by the severity of self and interpersonal dysfunction in terms of personality functioning (PF) and an optional assessment of specific maladaptive personality trait expressions. Also, somatoform disorders are replaced by somatic symptom disorder (SSD). This study examines associations using the novel diagnostic criteria of SSD in an unselected primary care sample, PF, and maladaptive traits in patients with and without SSD. Methods: An anonymized cross-sectional study was conducted. A questionnaire including SSD-12 (Somatic Symptom Disorder B Criteria Scale-12) and PHQ-15 (Patient Health Questionnaire-15), LPFS-BF 2.0 (Level of Personality Functioning Scale - Brief Form) and PID-5BF+M (Modified Personality Inventory for DSM-5 - Brief Form Plus) was used. A bifactor (S-1) model was calculated with PF (reference for general factor) and personality traits (specific factors) to estimate associations between PF, specific maladaptive personality traits, and SSD. Differences in personality scales between SSD and non-SSD patients were calculated with the Mann-Whitney U test. Results: A total of 624 patients in six general practices participated (mean age 47 years; 60.4% female). SSD-12 and PHQ-15, respectively, showed significant associations with PF (γ = 0.51; γ = 0.48; p < 0.001), negative affectivity (γ = 0.50; γ = 0.38, p < 0.001) and psychoticism (γ = 0.29; γ = 0.28; p < 0.010). Besides, SSD-12 was significantly associated with disinhibition (γ = −0.38; p < 0.010) and anankastia (γ = −0.16; p < 0.010). Patients with SSD showed significantly impaired PF and maladaptive traits in all scales (p < 0.001). Conclusion: Impaired PF explains moderate to large amounts of the SSD symptoms and maladaptive personality traits negative affectivity, psychoticism, disinhibition, and anankastia show specific associations beyond PF. An in-depth understanding of these relations might be helpful to improve doctor-patient communication and treatment in SSD.
Online verfügbar: 6. September 2024
Gesehen am 04.03.2025